2015
DOI: 10.1167/iovs.15-16914
|View full text |Cite
|
Sign up to set email alerts
|

Does Myopia Affect Angle Closure Prevalence

Abstract: PURPOSE. To conduct a simulation study to estimate the prevalence of occludable angle (OA), a surrogate for primary angle closure glaucoma (PACG), with the increased rate of myopia in the Chinese population. METHODS.People with phakic eyes in Liwan Eye Study were included as the study sample. Anterior chamber depth (ACD) was measured before dilation by A-mode ultrasound and OA was evaluated with static gonioscopy. Random sampling was used to generate 50 cohorts with sample size of 200 for each of myopic rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
5
16
1
Order By: Relevance
“…For example, shallow ACD is the most important risk factor for occludable angle, and the ACD in He Ming Guang’s study was shallower than that in our study. The mean ACD in He Ming Guang’s study increased from 2.68 mm to 2.74 mm when the prevalence of myopia increased from 10% to 60% [ 11 ], whereas in our study, the mean ACD increased from 2.83 (hyperopia group) to 3.08 (myopia group). This shows that the upper limit of the mean ACD in their study (2.74 mm, 60%myopia) was still shallower than the lower limit of the mean ACD (2.83 mm, 100% hyperopia) in our study.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…For example, shallow ACD is the most important risk factor for occludable angle, and the ACD in He Ming Guang’s study was shallower than that in our study. The mean ACD in He Ming Guang’s study increased from 2.68 mm to 2.74 mm when the prevalence of myopia increased from 10% to 60% [ 11 ], whereas in our study, the mean ACD increased from 2.83 (hyperopia group) to 3.08 (myopia group). This shows that the upper limit of the mean ACD in their study (2.74 mm, 60%myopia) was still shallower than the lower limit of the mean ACD (2.83 mm, 100% hyperopia) in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…However, Kai-lin Yong reported that almost one quarter of angle-closure patients were myopic [ 7 ]. He Ming Guang reported that the increasing prevalence of myopia has minimal impact on the prevalence of occludable angles, with myopia increasing from 10% to 60% and narrow angle prevalence decreasing from 11.1% to 9.6% [ 11 ]. The difference between our study and Kai-lin Yong’s study may associate with subject selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Singaporean study showed that almost one-quarter of PAC was myopic, 5 whereas a Malaysian investigation found that the distribution of myopia was approximately 37% in PAC patients. 6 Jin et al 7 concluded that the increasing prevalence of myopia has minimal influence on the angle-closure prevalence. It seems that we are going to have more myopic PAC with the rise of myopia in the world, especially in East Asia.…”
mentioning
confidence: 99%
“… 3 , 4 However, simulation analysis of the Liwan Eye Study reported that the myopia had minimal effect on PACG prevalence. 5 Recent studies, on the other hand, have highlighted that a significant proportion of patients with PACG have myopia, with approximately one-third of rural patients with PACG in rural China having myopia, and nearly 37% of patients with PACG in Malaysia having myopia. 6 , 7 PACG can also occur in high myopic eyes, with 1.9% to 2.6% of patients with PACG are highly myopic.…”
Section: Introductionmentioning
confidence: 99%